PROCESS CAPABILITIES ANALYSIS - CASE STUDY - Liviu Marius CÎRȚÎNĂ; Constanța RĂDULESCU (Fiabilitate şi Durabilitate)
This paper presents an analysis of the capability of manufacturing processes for a characteristic of a product. The characteristic pursued Ø11 with a tolerance of ± 0,1 mm. Statistical control will make it possible to analyze the processes, if they are controllable and efficient. The analysis of the stability of a technological process by means of the selected characteristics is carried out in stages by repeated sampling, extracting, at predetermined intervals, k samples with sufficiently large volume. Quantitative assessment of the performance capacity of a technological process is achieved by determining performance indices.